Can Fiscal Externalities Be Internalized? - Luttmer, Erzo F. P. (National Bureau of Economic Research, 2022)
Subsidies and in-kind transfers give rise to negative fiscal externalities. However, internalizing negative fiscal externalities through taxation would undo the subsidy or in-kind transfer that caused them. Similarly, positive fiscal externalities cannot be internalized though government subsidies. This paper describes a mechanism that transfers fiscal externalities from the government to private parties. Such transfers generate incentives within the private sector to reduce inefficiencies caused by fiscal externalities. Thus, the paper offers a straightforward, but powerful, insight: transferring fiscal externalities to third parties extends the reach of the Coase Theorem to inefficiencies stemming from fiscal externalities
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Subvention; Externer Effekt; Verteilungswirkung; Coase-Theorem; Institutions: Design; Formation; Operations; and Impact; General; Externalities; Redistributive Effects; Environmental Taxes and Subsidies; Social Innovation